An overview of power quality enhancement techniques applied to distributed generation in electrical distribution networks. (October 2018) - Naderi, Yahya; Hosseini, Seyed Hossein; Ghassem Zadeh, Saeid; Mohammadi-Ivatloo, Behnam; Vasquez, Juan C.; Guerrero, Josep M.
Abstract: It is obvious that power quality is an important characteristic of today's distribution power systems as loads become more sensitive on the other hand nonlinear loads are increasing in the electrical distribution system. Considering the distributed nature of harmonic loads, the need for distributed power quality improvement (PQI) is inevitable. From years ago, researchers have been working on various kinds of filters and devices to enhance the overall power quality of power system, but today the nature of distribution system has been changed and power electronic based DGs play an important role in distribution grids. In this paper, a thorough survey is done on power quality enhancement devices with emphasis on ancillary services of multi-functional DGs. A literature review is also done on microgrids concept, testbeds and related control methods. Although there were some applications of DGs for PQI improvement these applications were not defined multi-functional DGs. Various control methods are studied and categorized regarding different viewpoints in the literature. Finally, a couple of thorough comparisons are done between the available techniques considering the nature, capabilities, advantages and implementation costs.